Dari Ulama Ke Internet: Pergeseran Sumber Dakwah di Era Digital - Kango, Andries; Syam, Muh. Taufiq; Mahmuddin, Mahmuddin; Fata, Ahmad Khoirul (Farabi, 2024)
This article discusses the transformation of dakwah (Islamic preaching) from conventional methods to digital, known as cyberdakwah, in the modern era. Digital dakwah has become a global phenomenon by leveraging internet technology, allowing Islamic messages to be spread more widely and efficiently. Society now has easier access to religious information through social media and search engines like Google, which has replaced the traditional role of scholars in providing religious knowledge. This phenomenon leads to a paradigm shift in acquiring dakwah knowledge, moving from religious scholars and institutions to digital platforms. The article examines the impact of this shift, including the incommensurability between knowledge from scholars and Google, as well as the sudden change in the patterns of seeking religious information. While cyberdakwah holds great potential, challenges arise regarding the superficiality of messages and the lack of personal connection between the preacher and the audience. Therefore, integrating digital and conventional dakwah is seen as essential to ensure that dakwah messages are received more deeply and responsibly.